OF SOCIAL PSYCHOLOGY AND OTHER DANGERS - Painter, Desmond (PINS-Psychology in Society, 2025)
Hogg, M A & Cooper, J (eds) (2003) The SAGE Handbook of Social Psychology. London: Sage. ISBN 0-7619-6636-6. Pages 526. Hogg and Cooper, in their “Preface and Introduction”, offer a brief description of the scientific genre this book belongs to: “Handbooks describe the state of the art – they survey what we know about social psychology, and in so doing identify gaps in our knowledge, current foci of research activity, and future research directions” (pxvii).